PENGELOLAAN PEMBELAJARAN MATEMATIKA MODEL SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) PADA SISWA MA - Susi Afriyeni (Manajer Pendididikan, 2016)
Learning success is supported by the selection model of learning by the teacher , so the teacher professionalism required in choosing a model of learning in the classroom . This research was conducted in the city of Bengkulu MAN 2 in the school year 2015-2016 is class XI and class that became population IPA X 1 is a sample of this research. Instrument tests taken by students in cycle 1 and cycle 2 continued with a follow-up of the cycle to 2. Election learning model Survey, Question, Read, Recite , Reviuw ( SQ3R ) very appropriately chosen to improve learning outcomes . Seen an increase in student learning outcomes , namely the achievement of 69 % to 77  % . So that these models can dikatan successful in improving student learning outcomes .